Decoding Qur'anic Linguistics through Fi'il Tsulasi Mazid in Surah Az-Zukhruf: Menguraikan Linguistik Al-Qur'an melalui Fi'il Tsulasi Mazid dalam Surat Az-Zukhruf - Nashrulloh, Mohammad Muzakki; Fauji, Imam (Indonesian Journal of Education Methods Development, 2024)
This study examines the occurrences and benefits of fi'il tsulasi mazid (trilateral verbs with additional letters) in Surah Az-Zukhruf, focusing on Arabic language learning and Qur'anic comprehension. Through a detailed analysis, we identified 57 instances of these verbs and categorized them based on their forms and types. Results indicate that the most common verb types are af'ala yuf'ilu and ifta'ala yafta'ilu, while others include fa'ala yufa'ilu and faa'ala yufaa'ilu. Various benefits of these verb forms, such as litta'diyah, littikhad, and littahawul, were identified. This research provides valuable insights for Arabic language educators, allowing them to better explain linguistic changes and improve students' understanding of Arabic as the language of the Qur'an. Hightligh: 1. Detailed Analysis: Studying 57 instances of fi'il tsulasi mazid.2. Common Verb Types: Identifying prevalent verb types.3. Educational Implications: Enhancing Arabic language teaching for Qur'anic comprehension. Keywords: Arabic linguistics, Qur'an, Fi'il tsulasi mazid, Surah Az-Zukhruf, Language education